2020
DOI: 10.3390/ijms21239055
|View full text |Cite
|
Sign up to set email alerts
|

Secretome Analysis of Inductive Signals for BM-MSC Transdifferentiation into Salivary Gland Progenitors

Abstract: Severe dry mouth in patients with Sjögren’s Syndrome, or radiation therapy for patients with head and neck cancer, significantly compromises their oral health and quality of life. The current clinical management of xerostomia is limited to palliative care as there are no clinically-proven treatments available. Previously, our studies demonstrated that mouse bone marrow-derived mesenchymal stem cells (mMSCs) can differentiate into salivary progenitors when co-cultured with primary salivary epithelial cells. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Table 1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21] summarizes the stem cell sources, differentiation methods and SG protein markers in the selected papers, arranged in the order of year published. Review article…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21] summarizes the stem cell sources, differentiation methods and SG protein markers in the selected papers, arranged in the order of year published. Review article…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanism of MSCs for the treatment of SGH has not yet been fully clarified. On the one hand, MSCs are able to differentiate directly into salivary gland acinar cells, which holds promise for alleviating SGH by regenerating salivary glands (Lim et al, 2013;Adine et al, 2018;Mona et al, 2020;Yan et al, 2020;Tran et al, 2022). On the other hand, transplantation of MSCs can upregulate the release of anti-inflammatory cytokines and downregulate the release of pro-inflammatory cytokines, while regulating T cells, B cells, dendritic cells, and natural killer cells to perform anti-inflammatory and immune regulation effects (Chihaby et al, 2021).…”
Section: Treatment By Direct Transplantation Of Pscderived Mscsmentioning
confidence: 99%
“…Since there is no clinically proven treatment, clinical management of xerostomia is limited to preventive treatment. Previous research has shown that mesenchymal stem cells (MMSC) derived from mouse bone marrow differ from salivary progenitors when grown together with mouse salivary epithelial cells [56]. Restrictive transcription factors in co-grown MMSCs are identified with amylase (AMY1), muscarinic 3 receptors (M3R), aquaporin 5 (AQP5), tubular morphological changes, and acinar cell marker expression [56].…”
Section: Applicationsmentioning
confidence: 99%
“…Mona et al, 2020, investigated inducible molecules in a conditioned medium that can trigger MMSC replication and integrated mass spectrometry and systems biology by high performance liquid chromatography. Based on their key roles in embryonic development and salivary gland growth, our method identified ten differentially expressed proteins [56]. In addition, systems biology analysis revealed six candidate proteins, namely cysteine-rich insulin-like growth factor binding protein 7 (IgFPP7), pro-angiogenic stimulant 61 (CYR61), acrin (AGRN), laminin, beta 2 (LAMP2), folistatin 1 (FSDL1) and fibronectin 1 (FN1), all of which could potentially contribute to the propagation of MMSC during co-cultivation [56].…”
Section: Applicationsmentioning
confidence: 99%